Fiscal Administration Variables and Productivity of State Universities and Colleges in Western Visayas, Philippines - Delfin, Nilo D. (JPAIR Multidisciplinary Research, 2015)
Funds, whether from government or generated by institutions from other sources are the lifeblood of institutional development. Since there is never an end to development and improvement, fund sourcing and allocation are continuing concerns of every educational institution. The study determined the financial variables and productivity of SUCs in Region VI for CY 2002-2003. The study aimed to determine the a) institutional profile of the 11 SUCs in Region VI, b) profile of financial managers of SUCs in Region VI, c) budgetary allocation based on the General Appropriations Act (GAA) and income from the Special Trust Fund (STF), and d) how these financial resources are utilized for the operation. Descriptive method of research was employed and data were analyzed through frequency count and percentage mean. Study revealed that 11 SUCs in Region VI shared a common vision of becoming the center excellence, research, extension, and production with a mission of producing globally competitive graduates. The West Visayas State University (WVSU) had the biggest budgetary allocation from GAA, and got the highest earnings in school fees. A similar pattern of expenditures had been adopted by the 11 SUCs in Region VI. The SUCs in the region foresee their respective institutions as Center of Excellence. Fiscal managers had upgraded their educational qualifications. Faculty members have conducted extension, income generating projects and published researches.
Keywords: Fiscal Administration; SUCs productivity; descriptive research; Western Visayas; Philippines